Bilateral and Symmetrical Anteromedial Bowing of the Lower Limbs in a Patient with Neurofibromatosis Type-I - Ali Al Kaissi; Klaus Klaushofer; Franz Grill; Rudolf Ganger (Case Reports in Orthopedics)
An 8-year-old girl was referred to our department because of generalized bowing of long bones (radii, ulnae, and femora) and significant bilateral and symmetrical posteromedial bowing of the tibiae and fibulae. The femora were laterally bowed whereas the tibiae and fibulae showed posteromedial bowing between the middle and distal thirds of the tibia with posterior cortical thickening effectively causing the development of bilateral congenital anterolateral bowing of the tibiae and fibulae. We referred to closing-wedge osteotomy of the left tibia along with fibular osteotomy in order to realign the deformity. Due to the delayed appearance of skin stigmata in her early life, the diagnosis of neurofibromatosis was ruled out. At the age of 9 years, café-au-lait spots and axillary freckling were apparent. Genetic tests confirmed von Recklinghausen disease (neurofibromatosis type-I (NF1)) (gene has been localised to 17q22). Interestingly, bilateral and symmetrical anteromedial bowing of the tibiae and fibulae has not been described in patients with NF-I.